Dengue in Colombia (Mathematical models for understanding dengue fever, 2025)
This chapter describes the general aspects of the dengue virus, from its biology to the epidemiology of the disease in Colombia and the world, with a broad overview of the insect vectors that transmit it. The two main mosquitoes that transmit the dengue virus are described, as well as aspects of their biology, chemical control with insecticides, molecular and biochemical mechanisms of resistance to them. Finally, a description is made of the mosquito strains isolated from different regions of Colombia and their main biological characteristics. This work, developed by the Biology and Infectious Diseases Research Group of the University of Antioquia (Medellín), offers a comprehensive view of dengue in Colombia.